2017
DOI: 10.1016/j.jclepro.2016.11.124
|View full text |Cite
|
Sign up to set email alerts
|

Eco-innovation and benchmarking of carbon footprint data for vineyards and wineries in Spain and France

Abstract: Environmental sustainability in the wine sector has become a priority, as a result of both the growing interest in environmental issues and the consumer's demand for more information regarding the environmental impact of the products they purchase. In this context, the use of carbon footprint as an indicator to assess and report the environmental burdens associated with wine production has gained a role of primary interest. The present study has the aim of improving the wine sector's sustainability by providin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 47 publications
7
63
0
3
Order By: Relevance
“…The increasing attention to sustainability is pushing the construction sector to build more sustainable buildings (Navarro et al ). In this regard, the wine sector has placed environmental sustainability in a priority position, due to both the consumer's demand for more information regarding the environmental impact of their purchases and the growing interest in environmental issues (Moscovici and Reed ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The increasing attention to sustainability is pushing the construction sector to build more sustainable buildings (Navarro et al ). In this regard, the wine sector has placed environmental sustainability in a priority position, due to both the consumer's demand for more information regarding the environmental impact of their purchases and the growing interest in environmental issues (Moscovici and Reed ).…”
Section: Methodsmentioning
confidence: 99%
“…The global dissemination of sustainability indexes and that of their configurations are treated as proxy variables for the appraisal of ‘green buildings’. Current evaluation systems range from energy utilisation assessment systems to life cycle analysis and total quality evaluation schemes (Navarro et al ); improving energy efficiency is the underlying factor behind them.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Respecto al cálculo de la huella de carbono, para fines de este trabajo se consideró el análisis del Alcance 1 y Alcance 2, que corresponden aproximadamente al 10% del total de la huella, alcanzando un valor de 0,22 kg CO2 equivalente/litro de vino [17,18]. En relación a los valores th World Congress of Vine and Wine obtenidos, se debe verificar la información reportada por parte de las viñas pilotos ya que son muy bajos en comparación a los referencias lo que hace inferir que la información se encuentra incompleta.…”
Section: Huella De Carbonounclassified
“…Other studies considered only specific indicators, especially the carbon footprint (CF) and the water footprints (WF) [28][29][30]. Extensive reviews on the application of the carbon footprint concept to wine production can be found in the literature [32][33][34][35]. Both indicators are directly linked to various key aspects of wine production such as energy consumption, land management and transportation related to the CF, and water usage for the WF.…”
Section: Introductionmentioning
confidence: 99%